Scaffold Protein Lnx1 Stabilizes EphB Receptor Kinases for Synaptogenesis - Li, Na; Chen, Si; Xu, Nan-Jie; Sun, Suya; Chen, Jin-Jin; Liu, Xian-Dong (Frontiers in Molecular Neuroscience, 2022)
Postsynaptic structure assembly and remodeling are crucial for functional synapse formation during the establishment of neural circuits. However, how the specific scaffold proteins regulate this process during development of the postnatal period is poorly understood. In this study, we find that a scaffold protein, ligand of Numb protein X 1 (Lnx1), deficiency leads to abnormal development of dendritic spines and formation of functional synapse. We further demonstrate that loss of Lnx1 promotes EphB receptors internalization from the cell surface. Constitutively active EphB2 intracellular signaling rescues synaptogenesis in Lnx1 mutant mice. Our data thus reveal molecular mechanism whereby Lnx1-EphB complex controls postsynaptic structure for synapse maturation during the adolescent period.